PHBS HEALTH EDUCATION FOR PREVENTION OF TRANSMISSION OF COVID 19 FOR FAMILIES WITH ELDERLY - Maria Ulfah; Tinah Purwaningsih Purwaningsih; Ahmad Baequny (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2022)
The elderly are a group affected by COVID-19, the elderly are more at risk of contracting Covid-19 because the immune system in the elderly is different from that of adults, so education is needed to prevent the transmission of COVID-19 in the elderly. The purpose of the activity is to provide education about preventing the transmission of COVID-19 to families with the elderly. The target of community service is families with the elderly who live in the Debong Lor village, Tegal City. The implementation is carried out by means of education, demonstration, and simulation of PHBS. The activity was carried out for 4 weeks and was attended by 40 families with the elderly. The results of the activity showed an increase in knowledge, namely before the activity the participants had less knowledge about COVID-19 (17.5%) and had good knowledge (32.5%), after the activity had good knowledge (80%) and lacked knowledge (7.5%), knowledge about PHBS most of the participants have less knowledge (25%) and have good knowledge (30%) after activities with good knowledge (85%) and poor knowledge (10%). It can be concluded that community service activities are able to increase knowledge and understanding of the community, especially families with the elderly about PHBS to prevent transmission of COVID-19 in the elderly. It is recommended for cadres to implement PHBS in the daily life aspects of the elderly and prevent the transmission of COVID-19 in the elderly.